The Effect of Fly Ash-Based Geopolymer Proportion on the Specific Gravity of Mixed Soil - Fathonah, Woelandari; Kusuma, Rama Indera; Mina, Enden; Baehaki, Baehaki; Rizka, Bella (JURUSAN TEKNIK SIPIL, 2024)
Road construction planning must consider the characteristics and strength of the soil. This study aims to determine the classification of soil and the effect of fly ash-based geopolymer as an added material on the specific gravity of soil. Specific gravity testing was carried out using a pycnometer to obtain the specific gravity of the soil. The test object used is a soil sample added with geopolymer with fly ash as raw material and an alkaline activator (Na2SiO3and NaOH). The NaOH concentration is 10 M with a solution ratio of 2.0 (Na2SiO3 to NaOH), fly ash content of 20%, and variations in S / L (fly ash to activator) levels of 1/2 and 1/2.5. Based on the research that has been done, the results show that the soil used in the study is included in the organic clay soil with a specific gravity value of 2.49. The effect of fly ash-based geopolymer in this study increases the specific gravity value, with a specific gravity of 2.60 for variation B (80% soil, 20% FA, S/L 1/2) so that the soil falls into the organic clay category and 2.69 for variation C (80% soil, 20% FA, S/L 1/2.5) so that the soil falls into the non-organic clay category.